Metformin Protects Against Diabetes-Induced Cognitive Dysfunction by Inhibiting Mitochondrial Fission Protein DRP1 - Hu, Yan; Zhou, Yile; Yang, Yajie; Tang, Haihong; Si, Yuan; Chen, Zhouyi; Shi, Yi; Fang, Hao (Frontiers in Pharmacology, 2022)
Objectives. Diabetes is an independent risk factor for dementia. Mitochondrial dysfunction is a critical player in diabetes and diabetic complications. The present study aimed to investigate the role of mitochondrial dynamic changes in diabetes-associated cognitive impairment. Methods. Cognitive functions were examined by novel object recognition and T-maze tests. Mice hippocampi were collected for electron microscopy and immunofluorescence examination. Neuron cell line HT22 and primary hippocampal neurons were challenged with high glucose in vitro. Mitotracker-Red CM-H2X ROS was used to detect mitochondrial-derived free radicals. Results. Diabetic mice exhibited memory loss and spatial disorientation. Electron microscopy revealed that diabetic mice had larger synaptic gaps, attenuated postsynaptic density and fewer dendritic spines in the hippocampus. More round-shape mitochondria were observed in hippocampal neurons in diabetic mice than those in control mice. In cultured neurons, high glucose induced a high phosphorylated level of dynamin-related protein 1(DRP1) and increased oxidative stress, resulting in cell apoptosis. Inhibition of mitochondrial fission by Mdivi-1 and metformin significantly decreased oxidative stress and prevented cell apoptosis in cultured cells. Treatment of Mdivi-1 and metformin restored cognitive function in diabetic mice. Conclusion. Metformin restores cognitive function by inhibiting mitochondrial fission, reducing mitochondrial-derived oxidative stress, and mitigating neuron loss in hippocampi of diabetic mice. The protective effects of metformin shed light on the therapeutic strategy of cognitive impairment.